An In Vivo Gain-of-Function Screen Identifies the Williams-Beuren Syndrome Gene GTF2IRD1 as a Mammary Tumor Promoter - Yongliang Huo (Cell Reports, 2016)
The broad implementation of precision medicine in cancer is impeded by the lack of a complete inventory of the genes involved in tumorigenesis. We performed in vivo screening of ∼1,000 genes that are associated with signaling for positive roles in breast cancer, using lentiviral expression vectors in primary MMTV-ErbB2 mammary tissue. Gain of function of five genes, including RET, GTF2IRD1, ADORA1, LARS2, and DPP8, significantly promoted mammary tumor growth. We further studied one tumor-promoting gene, the transcription factor GTF2IRD1. The mis-regulation of genes downstream of GTF2IRD1, including TβR2 and BMPR1b, also individually promoted mammary cancer development, and silencing of TβR2 suppressed GTF2IRD1-driven tumor promotion. In addition, GTF2IRD1 is highly expressed in human breast tumors, correlating with high tumor grades and poor prognosis. Our in vivo approach is readily expandable to whole-genome annotation of tumor-promoting genes.